Analisis Strategi Pengembangan Usaha Jamur Tiram Putih/Pleurotus Ostreatus (Studi Kasus: Nasabah Pembiayaan pada BSI di Kabupaten Langkat) - Silvia Amelia; Raja Sakti Putra Harahap; M. Lathief Ilhamy Nasution (Institut Syekh Abdul Halim Hasan Binjai, 2022)
White oyster mushroom is one of the most popular types of mushrooms and is widely consumed by the public, while Mr. Suherman's white oyster mushroom business has not been able to meet the demands of his customers. The researcher considers that Mr. Suherman's white oyster mushroom business needs to be developed by creating alternative strategies by taking into account the factors contained in Mr. Suherman's white oyster mushroom business in Kwala Begumit village. This study aims to determine the strategy for developing a white oyster mushroom business through SWOT analysis in Kwala Begumit Village, Stabat District, Langkat Regency. The theories used in this study consist of strategy, business development, business development strategy in the white oyster mushroom business, SWOT analysis, and the strategy for applying SWOT analysis to oyster mushroom businesses. This research is a qualitative research. Data collection techniques were obtained from interviews and documentation. While the data analysis technique used is the SWOT analysis technique. The research method used is a qualitative approach by collecting data through documentation, interviews.